The association of breathing pattern with exercise tolerance and perceived fatigue in women with systemic lupus erythematosus: an exploratory case–control study - Aldhahi, Monira I.; Wooten, Liana C.; Hasni, Sarfaraz; Mikdashi, Jamal; Keyser, Randall E. (Rheumatology international, 2022)
The aims of the study were to (1) to characterize the breathing pattern and work of breathing during peak exercise in patients with SLE; (2) to examine the extent to which the breathing pattern and work of breathing impact the exercise capacity and fatigue. Forty-one women participated in the study (SLE: n = 23, median = 35, range = 21–57 years, control: n = 18, median = 38, range = 22–45 years). Each subject performed a treadmill cardiopulmonary exercise test (a modified Bruce treadmill protocol) ending with volitional exhaustion. Breathing mechanic was characterized by measures of expired minute volume ( V E ), tidal volume ( V t), respiratory rate ( f ), work of breathing, and cardiorespiratory fitness was quantified by measures of peak oxygen consumption (VO 2 ) and time to exhaustion. Data presented as median and interquartile range (IQR). Women with SLE had lower V t {1221 [488.8] mL/min vs. 1716 [453.1] mL; p = .006}, V E {58.9 [18.9] L/min vs 70 [28.1] L/min, p = 0.04} and increased breathing frequency {51.5 [10.8] vs 43.6 [37.8] bpm, p = 0.01} compared to the control group. The time to exhaustion and peak VO 2 during the CPET were significantly reduced in those with SLE compared to controls {13.3 [10.2] vs 16.1 [2.2] min; p = 0.004}, {20 [6.1] mL/kg/min vs 26.6 [7] mL/kg/min p < 0.001}, respectively. Differences remained when the analyses were controlled for the observed differences in peak VO 2 . When the regression model adjusted for the peak VO 2 , it had been shown that V t, WOB and f were explained variances in the fatigue severity by 64% [ p < 0.001]. The decline in V E and V t coupled with a decreased peak VO 2, and work of breathing may have contributed to low cardiorespiratory fitness and fatigue in patients with systemic lupus erythematosus.